ENT 530 Social Media Portfolio : Gerobok.co / Nur Rabiatul Adawiyah Mohd Nizam - Mohd Nizam, Nur Rabiatul Adawiyah (2019)
Our business start commence in 2019 at Ayer Hitam where is stratergic location to do a business as it is near to one oflocal university.